KEMAMPUAN PEMAHAMAN MAHASISWA TINGKAT III PRODI DIII KEPERAWATAN DALAM MENYELESAIKAN ASUHAN KEPERAWATAN DENGAN PENERAPAN SDKI, SLKI DAN SIKI - ade rahman (Akper Kesdam I/Bukit Barisan Padang, 2021)
The Nursing Diploma III Education Program is a higher education program that aims to produce vocational nursing graduates who have special knowledge and abilities or skills in the field of nursing, and have a professional ethical attitude to be able to provide comprehensive nursing care to patients. It is important for students to understand the application of the SDKI, SIKI and SLKI to see how well they understand how to use the book in completing nursing care for patients. Respondents in this study were 3rd grade students totaling 46 people, the method used was quantitative by distributing questionnaires to students via google form. The results showed that most of the students had a high understanding of making a diagnosis, compiling outcomes and interventions. It is hoped that in the future students can apply this 3S in completing a Nursing Care.